Overexpression of AR‐regulated lncRNA TMPO‐AS1 correlates with tumor progression and poor prognosis in prostate cancer. Issue 16 (13th August 2018) - Huang, Wenhua; Su, Xinya; Yan, Wei; Kong, Zhe; Wang, Dan; Huang, Yan; Zhai, Qiaoli; Zhang, Xiaowei; Wu, Hai; Li, Yao; Li, Tao; Wan, Xuechao
Abstract : Background: Prostate cancer (PCa) is a leading cause of death in males all over the world; besides, the diagnosis and therapy of it are still challenging. Researchers have revealed that long non‐coding RNAs (lncRNAs) play important roles in the genesis and progression of human cancers, including PCa. Methods: Bioinformatics analysis and Kaplan‐Meier survival analysis were utilized to confirm TMPO‐AS1 as a diagnostic and prognostic marker. The TMPO‐AS1 levels in both patient tissues and PCa cell lines were determined by qRT‐PCR analysis. Moreover, the chromatin immunoprecipitation (ChIP) assay identified that TMPO‐AS1 was a direct target of AR. The effect of overexpression or knockdown of TMPO‐AS1 on cell proliferation, migration, cell cycle, and cell apoptosis was assessed by using CCK‐8, transwell assays, and flow cytometric analysis, respectively. Results: Based on primary screening, we found that TMPO‐AS1 could be a useful diagnostic and prognostic marker for PCa, whose expression was upregulated in PCa samples and associated with poorer prognosis. Bioinformatics predictions revealed TMPO‐AS1 was associated with a series of biological processes involved in PCa progression. In PCa cells, TMPO‐AS1 was predominantly localized in the cytoplasm and directly down‐regulated by AR. Gain/loss‐of‐function assays showed TMPO‐AS1 overexpression increased cell proliferation by promoting cell cycle progression and promoted migration, but reduced apoptosis of PCa cells. In addition, TMPO‐AS1 may be a diagnostic and prognostic marker in multiple cancer types. Conclusions: AR‐regulated lncRNA TMPO‐AS1 functioned as an oncogenic lncRNA in PCa, and may be a potential diagnostic and prognostic biomarker to be used as a therapeutic target for PCa.